Modern banking and OTC derivatives markets : the transformation of global finance and its implications for systemic risk - Schinasi, Garry J....[et al] (IMF WashingtonUS, 2000)
Highlights the key features of modern banking and OTC derivatives markets that seem to be relevant for assessing their functioning, their implications for systemic financial risks in the international financial system, and areas where improvements in ensuring financial stability can be obtained.